2014
DOI: 10.1310/hpj4910-923
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Vasospasm in Critically III Patients with Aneurysmal Subarachnoid Hemorrhage: Does the Evidence Support the Ever-Growing List of Potential Pharmacotherapy Interventions?

Abstract: The occurrence of cerebral vasospasm after aneurysmal subarachnoid hemorrhage (SAH) is a significant event resulting in decreased cerebral blood flow and oxygen delivery. Prevention and treatment of cerebral vasospasm is vital to avert neurological damage and reduced functional outcomes. A variety of pharmacotherapy interventions for the prevention and treatment of cerebral vasospasm have been evaluated. Unfortunately, very few large randomized trials exist to date, making it difficult to make clear recommenda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 145 publications
(178 reference statements)
0
5
0
Order By: Relevance
“…Intraarterial papaverine causes vasodilatation, likely related to alteration in cAMP. It can result in transient reversal of cerebral hypoperfusion with improvement in blood flow velocities and CBF . There are significant limitations with its use.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intraarterial papaverine causes vasodilatation, likely related to alteration in cAMP. It can result in transient reversal of cerebral hypoperfusion with improvement in blood flow velocities and CBF . There are significant limitations with its use.…”
Section: Resultsmentioning
confidence: 99%
“…This antioxidant effect is believed to confer a neuroprotective benefit in aSAH. 82,83 A trial that enrolled 1015 patients randomized to receive tirilazad at 6 mg/ kg/day demonstrated significantly reduced overall mortality (P < .01) and improved clinical outcomes at 3 months compared to patients who received placebo (P < .01). 84 The benefits of treatment with tirilazad were predominantly shown in men rather than in women.…”
Section: Tirilazadmentioning
confidence: 99%
See 1 more Smart Citation
“…Vasopressors are commonly used to maintain cerebral perfusion during delayed vasospasm in subarachnoid hemorrhage caused by aneurismal rupture, septic shock, and neurogenic shock. [ 10 , 11 ] Because vasopressors centralize the blood volume and increase blood supply to vital organs such as the brain and heart, they cause splanchnic hypoperfusion, which can exacerbate mesenteric ischemia. [ 9 , 12 ] In patients with multiple trauma in neurosurgical ICU, acute kidney injury due to rhabdomyolysis, acute kidney injury due to use of mannitol to control intracranial pressure, refractory metabolic acidosis, and acute kidney injury in septic conditions may occur.…”
Section: Discussionmentioning
confidence: 99%
“…Subarachnoid hemorrhage (SAH) is a type of blood oozing from damaged vessels into the subarachnoid space because of different kinds of brain damage. It is a destructive cerebrovascular disease that affects the cerebral blood perfusion state [ 1 ] and contributes to cerebral vasospasm [ 2 ], early brain injury [ 3 ], chronic cerebral ischemia [ 4 ], and various systemic complications [ 5 ]. These injuries often lead to a poor prognosis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%